The Simalungun Script in the Development of Cultural Heritage and Local Wisdom Learning Plans - Damanik, Ramlan; Sinaga, Warisman; Herlina; Purba, Asriaty r; Sinulingga, Jekmen (Raja Zulkarnain Education Foundation, 2025)
The Simalungun script is one of the intangible cultural heritages of the Simalungun Batak community, possessing significant historical, linguistic, and symbolic value. However, modern developments and the dominance of the Latin alphabet have led to a significant decline in its usage. This article aims to examine the role of the Simalungun script in cultural heritage development through a community-based preservation and revitalization approach. Utilizing Laurajane Smith’s (2006) theory of heritage preservation and an ecolinguistic perspective, this study analyzes strategies for strengthening the Simalungun script through education, digitalization, and integration into creative media. The research employs a descriptive method with a qualitative approach. The findings reveal that the Simalungun script can serve as a contextual and educational tool for cultural transformation and identity formation among younger generations. School involvement programs, the development of local curriculum, and the implementation of technology-based initiatives using the script have proven effective in raising awareness and enhancing cultural literacy skills. The study also identifies that the Simalungun script consists of 19 ina ni surat (main letters): a, ha/ka, ba, pa, na, wa, ga, ja, da, ra, ma, ta, sa, ya, nga, la, nya, i, and u. These characters are typically curved and angular, and are written from left to right on media such as tree bark, bamboo, or bone. Additionally, eight anak ni surat (derived letters) are recognized: haluan, haboritan, hatalingan, sihorlu, hamisaran, hatulungan, hajoringan, and panongon. Therefore, preserving the Simalungun script is not merely an act of conservation, but a dynamic strategy for the development of cultural heritage that is adaptive to the times.